The Cambria Connection: Identifying Ceramic Production and Community Interaction in Late Prehistoric Minnesota, AD 1050-1300 - (:unkn) unknown (My University, 2016)
The Cambria phase (AD 1050-1300) is an archaeological complex primarily centered on the elevated terraces of the Minnesota River in south-central Minnesota. Cambria phase pottery demonstrates technical and stylistic influences from several different late prehistoric cultures, and although the Cambria phase is currently classified as part of the Initial Middle Missouri Variant, certain affinities are evident between the grit-tempered, rolled rim ceramics at Cambria and the Powell-Ramey series at Cahokia. Although this pottery is a minority ware at Cambria, it is ubiquitous in the site literature, where it is interpreted as evidence for interaction with the Mississippian world. However, the nature and degree of the relationship between the two cultural areas has never been defined clearly. This project utilizes attribute and compositional analysis to identify the range of variation in the ceramic assemblages of three sites referred to collectively as the Cambria Locality: the Cambria, Price, and Owen D. Jones sites. A theoretical framework is structured from integrating articulated facets of world systems theory, community studies and the internal frontier concept. The results are interpreted at multiple levels of analysis, but are primarily focused on understanding interaction locally amongst the three sites, and in a micro-regional context within southern Minnesota. The evidence for and mechanisms of cultural interaction with Mississippian communities are evaluated. Finally, a model is developed to explain the emergence of the Cambria Locality village sites as intra-regional migration by cultural groups trending towards sedentism and maize agriculture from other areas in southern Minnesota.
Keywords: Cambria; Ceramics; Late Prehistoric; Minnesota; World Systems Theory; X-Ray Fluorescence (xrf)